PERKEMBANGAN BAHASA ANAK TUNARUNGU DI SMA-LB PERTIWI DAN RELEVANSINYA DALAM PEMBELAJARAN BAHASA INDONESIA DI SMA-LB - Candra Ratna Sari; Doni Uji Windiatmoko; Taswirul Afkar (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2018)
This study aims to describe the development of the language of children with hearing impairment of phonological, morphological and syntactic structures, and their relevance in learning Indonesian in SMA-LB. Objects studied are deaf children in SMA-LB PERTIWI Mojokerto city. This research uses qualitative research type, using psycholinguistic approach. The form of research is descriptive qualitative, ie data collected in the form of words or sentences to describe the focus of research or problem, analyze it on existing data. Data collection in this study by observation, interview, record and record. Data analysis techniques used are data reduction, data display, and conclusion. The results of the data are analyzed and sorted out for inclusion in the data card and summarizes the results of the data analysis. Validity of data in this study using triangulation theory, source triangulation, and triangulation method. The results of the study indicate that: (1) The development of the language of children with hearing impairment phonologically, the articulation is quite clear although there are often various errors in the mention of sentences or words, (2) The development of the language of children with hearing impaired morphologically, ATR is easier to generate free morphemes than bound morphemes, morpheme bound to a child with hearing impairment is only able to create prefixes, confixes and suffixes, bound morphemes appear optimally when ATR repeats the phrase repeatedly, (3) The development of the language of a deaf child syntactically has been able to make one sentence or more, but the child is deaf when making sentences (4) The relevance of language development to Indonesian language learning in SMA-LB so that students are better able to develop language skills. Keywords: language development, phonology, psycholinguistics